Design and development of soft robotic hand for vertical farming in spacecraft - Suresh, Aswath; Udupa, Ganesha; Gaba, Dhruv (Institute of Advanced Engineering and Science, 2020)
For colonization in deep space we need to explore the feasibility of a bioregenerative system in microgravity or artificial gravity environments. The process has various complexities form ranging to biological obstacles to engineering limitations of the spacecraft. Concentration of microbes in the confinements of a spacecraft can be fatal for the crew. In this paper, a solution to the elevated microbial levels by farming using robots is discussed. The soft robotic arm is made up of Asymmetric Flexible Pneumatic Actuator (AFPA). The AFPA under internal pressure will curve in the direction of the side having greater thickness as the expansion of the thinner side (outside radius) will be more than thicker side (inside radius) due to differential expansion and moment induced due to eccentricity. Simulation results demonstrate that bending based on AFPA can meet the designed requirement of application. The AFPA is used for five fingers of the robotic hand. The safe, soft touch and gentle motion of the bellow (AFPA) gives the feel of real human hand. The internal pressure of the AFPA is controlled using a solenoid valve which is interfaced using an Arduino microcontroller for hand like moves. The bending of the fingers and degree of freedom (DOF) of the joints of the hand is controlled using an IMU and flex sensor. Wireless connection of the hand and the control system is implemented using XBee pro 60mW with a range of 1 miles. The pneumatic soft robotic hand is made up of solenoid valve, Mini Compressor, AFPA bellow, and Servos. This soft robotic hand has many advantages such as good adaptability, simple structure, small size, high flexibility and less energy loss. As an extension Manual control of the robot using a virtual reality environment and well as some possible aspects of an automated farming systems can be considered as future additions.